2014
DOI: 10.1007/s10915-014-9832-2
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Solution Point Coordinates for Flux Reconstruction Schemes on Triangular Elements

Abstract: The flux reconstruction approach offers an efficient route to high-order accuracy on unstructured grids. The location of the solution points plays an important role in determining the stability and accuracy of FR schemes on triangular elements. In particular, it is desirable that a solution point set (i) defines a well conditioned nodal basis for representing the solution, (ii) is symmetric, (iii) has a triangular number of points and, (iv) minimises aliasing errors when constructing a polynomial representatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Takex u ei to be a set of standard element solution points associated with a given element type, where 0 ≤ i < N e . Examples of such point distributions are Gauss-Legendre or GaussLobatto points, when N D = 1, Witherden-Vincent points [22] for triangles, when N D = 2, and Shunn-Ham points [23] for tetrahedra, when N D = 3. The set of solution pointsx u ei within the standard element Ω e can be used to define a nodal basis set l ei (x) of order P(N e ) that spans a polynomial space P .…”
Section: Flux Reconstructionmentioning
confidence: 99%
“…Takex u ei to be a set of standard element solution points associated with a given element type, where 0 ≤ i < N e . Examples of such point distributions are Gauss-Legendre or GaussLobatto points, when N D = 1, Witherden-Vincent points [22] for triangles, when N D = 2, and Shunn-Ham points [23] for tetrahedra, when N D = 3. The set of solution pointsx u ei within the standard element Ω e can be used to define a nodal basis set l ei (x) of order P(N e ) that spans a polynomial space P .…”
Section: Flux Reconstructionmentioning
confidence: 99%
“…Following Witherden and Vincent [12] we will use this property to define the truncation error associated with an N p point rule…”
Section: Basis Polynomialsmentioning
confidence: 99%
“…The traditional objective when constructing quadrature rules is to obtain a rule of strength φ inside of a domain using the fewest number of points. To this end efficient quadrature rules have been derived for a variety of domains: triangles [4][5][6][7][8][9][10][11][12][13], quadrilaterals [11,14,15], tetrahedra [7,9,16,17], prisms [18], pyramids [19], and hexahedra [11,[20][21][22]. For finite element applications it is desirable that (i) points are arranged symmetrically inside of the domain, (ii) all of the points are strictly inside of the domain, and (iii) all of the weights are positive.…”
Section: Introductionmentioning
confidence: 99%
“…This change gave rise to a marked improvement in both stability and accuracy. These results were subsequently confirmed by Witherden and Vincent [8] in 2014 who analysed the performance triangular quadrature rules when used as solution points. Inside of tetrahedra Williams [7] compared the three dimensional α-optimised points against the tetrahedral quadrature rules of Shunn and Ham [12].…”
Section: Quadrature Rulesmentioning
confidence: 65%
“…It has been demonstrated, both theoretically [5] and empirically [6][7][8] that the degree of aliasing driven instabilities depends upon the location of the solution points inside each element. Specifically, it has been found that placing points at the abscissa of strong Gaussian quadrature rules has a positive impact on their performance.…”
Section: Introductionmentioning
confidence: 99%